Respuesta :

[tex] \huge \boxed{\mathbb{QUESTION} \downarrow}[/tex]

  • Simplify the expression (7-(-1 ))²+(-2)²

[tex] \large \boxed{\mathfrak{Answer \: with \: Explanation} \downarrow}[/tex]

[tex] \sf \: ( 7 - ( - 1 ) ^ { 2 } ) + ( - 2 ) ^ { 2 }[/tex]

Calculate -1 to the power of 2 to get 1.

[tex] \sf \: 7-1+\left(-2\right)^{2} [/tex]

Subtract 1 from 7 to get 6.

[tex] \sf \: 6+\left(-2\right)^{2} [/tex]

Calculate -2 to the power of 2 to get 4.

[tex] \sf \: 6+4 [/tex]

Add 6 and 4 to get 10.

[tex] = \boxed{\boxed{\bf \: 10}}[/tex]

Hey there!

(7 - (-1))² + (-2)²

= 7 - 1 + (-2)²

= 6 - 2²

= 6 - 4

= 10

Hope it helps ya!